Thapsigargin-Stimulated LAD2 Human Mast Cell Line Is a Potent Cellular Adjuvant for the Maturation of Monocyte-Derived Dendritic Cells for Adoptive Cellular Immunotherapy - Taborska, Pavla; Stakheev, Dmitry; Bartunkova, Jirina; Smrz, Daniel (International journal of molecular sciences, 2021)
The preparation of dendritic cells (DCs) for adoptive cellular immunotherapy (ACI) requires the maturation of ex vivo-produced immature(i) DCs. This maturation ensures that the antigen presentation triggers an immune response towards the antigen-expressing cells. Although there is a large number of maturation agents capable of inducing strong DC maturation, there is still only a very limited number of these agents approved for use in the production of DCs for ACI. In seeking novel DC maturation agents, we used differentially activated human mast cell (MC) line LAD2 as a cellular adjuvant to elicit or modulate the maturation of ex vivo-produced monocyte-derived iDCs. We found that co-culture of iDCs with differentially activated LAD2 MCs in serum-containing media significantly modulated polyinosinic:polycytidylic acid (poly I:C)-elicited DC maturation as determined through the surface expression of the maturation markers CD80, CD83, CD86, and human leukocyte antigen(HLA)-DR. Once iDCs were generated in serum-free conditions, they became refractory to the maturation with poly I:C, and the LAD2 MC modulatory potential was minimized. However, the maturation-refractory phenotype of the serum-free generated iDCs was largely overcome by co-culture with thapsigargin-stimulated LAD2 MCs. Our data suggest that differentially stimulated mast cells could be novel and highly potent cellular adjuvants for the maturation of DCs for ACI.
Keywords: imunoterapie adoptivní; Monocytes; monocyty; Cell Culture Techniques; Antigen Presentation; Humans; Cell Differentiation; Immunotherapy, Adoptive; prezentace antigenu; mastocyty; adjuvancia imunologická; Coculture Techniques; buněčné kultury; thapsigargin; Thapsigargin; Dendritic Cells; ženské pohlaví; dendritické buňky; lidé; Adjuvants, Immunologic; buněčná diferenciace; Mast Cells; kokultivační techniky; Female